EFEKTIVITAS PEMBELAJARAN DARING DENGAN MENGGUNAKAN GOOGLE CLASSROOM (GCR) PADA MATA KULIAH KONSEP DASAR IPA MAHASISWA PGSD - Hotma Tiolina Siregar; Rupina M. Tarigan (Journal of Natural Sciences, 2020)
This study aims to describe the effectiveness of online learning using the Google Calss Room (GCR) online media during the Covid-19 pandemic in the Science Basic Concepts Course. This research is a descriptive quantitative study using online media, namely google form. The results of the study illustrated that students rated learning in the Science Basic Concepts Course using online media, namely Google Classroom (GCR) as very effective (15.6%), most of them rated it as effective (75%), and ineffective (9.4%).